Tính nhanh : 9 + 3 x 1
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`9/2xx7/3-4/3xx9/2`
`=9/2xx(7/3-4/3)`
`=9/2xx3/3`
`=9/2xx1`
`=9/2`
= (11+19)+(12+18)+(13+17)+(14+16)+15
=(30+30+30+30)+15
=120+15
=135
\(\dfrac{6}{7}\cdot\dfrac{8}{9}+\dfrac{7}{9}\cdot\dfrac{2}{7}-\dfrac{18}{21}\cdot\dfrac{1}{9}+\dfrac{7}{9}\cdot\dfrac{3}{7}\)
\(=\dfrac{6}{7}\cdot\dfrac{8}{9}-\dfrac{6}{7}\cdot\dfrac{1}{9}+\dfrac{7}{9}\left(\dfrac{2}{7}+\dfrac{3}{7}\right)\)
\(=\dfrac{6}{7}\left(\dfrac{8}{9}-\dfrac{1}{9}\right)+\dfrac{7}{9}\cdot\dfrac{5}{7}\)
\(=\dfrac{7}{9}\left(\dfrac{6}{7}+\dfrac{5}{7}\right)=\dfrac{7}{9}\cdot\dfrac{11}{7}=\dfrac{11}{9}\)
a, \(x^2-2.\frac{1}{3}x+\frac{1}{9}=\left(x-\frac{1}{3}\right)^2\)
Thay x = 9 vào ta được : \(=\left(9-\frac{1}{3}\right)^2=\left(\frac{26}{3}\right)^2=\frac{676}{9}\)
\(x^2-\frac{2}{3}x+\frac{1}{9}\)
Thay \(x=9\) và ta được:
\(9^2-\frac{2}{3}9+\frac{1}{9}\)\(=81-6+\frac{1}{9}\)\(=\frac{676}{9}\)
a: \(=\dfrac{4}{5}\cdot\dfrac{7}{3}\cdot\dfrac{3}{7}\cdot\dfrac{5}{4}+2011=2011+1=2012\)
b: \(=\dfrac{1}{3}\cdot\dfrac{9}{7}\cdot\dfrac{7}{9}=\dfrac{1}{3}\)
1, =4/9 x (3/7 + 2 x 4/7) - 1/9 - 3/9
= 4/9 x 1 - 1/9 - 3/9 = 0
2, = ( 22/5 x 5/22 ) x 12
= 1 x 12 = 12
9 + 3 x 1 =12 x 1
=12
34-65=